Pelatihan Kepemimpinan Pada Organisasi Intra Kampus - Sawabi Sawabi; Amri Nur Azizah; Dwi Reni Nisvul; Fanani Fanani; Alfarizi Alfarizi (CV. ALIM'SPUBLISHING, 2023)
Leadership training in student organizations still needs to be improved. This increase aims to improve the quality of intra-campus organizations. The methods used in this training are exploration, lecture and discussion. This event was attended by 48 participants from various semesters. As a result of this training, students have quite a lot of enthusiasm, because they can learn more about the goals and benefits of organizing on campus.